Pahang mosques and surau portal - A’dilah Hanum, Azman (2019)
In today's modernization era, most industries use the online system to access information, apply for jobs, loans and many other things. By using the Pahang Mosques and Surau Portal, people can get information about the mosque and surau in Pahang easily and Muslim tourists can know the mosque in Pahang. For local residents near the mosque or surau, they will not miss any activities organized by the mosque or surau near them with this system. Not only that, this system makes it easy for anyone who wants to donate to the mosque more easily and quickly through transfer on the account provided regardless of the distant. The objective of this system is to provide accurate and up-to-date information regarding mosques and surau in Pahang. This system also helps users to know the location of the mosque or surau in the map by connecting to Google maps and this system wants to help users to make donations more quickly and efficiently. The system was developed for the Pahang Islamic Religious Department (JAIP) to facilitate them to manage anything relating to the mosque and also to assist mosque or surau committee members to keep information that more accurate. Rapid Application Development (RAD) is a method or technique used to develop this system. There are four stages or phases in the RAD which are requirement phase, the design phase, the development phase and the cutover phase.